Employees’ Whistleblowing Intention in Public Sector: The Role of Perceived Organizational Support as Moderating Variable - Tito Agung Yuswono; Yanki Hartijasti (Journal of Accounting and Investment, 2018)
Whistleblowing has an important role in exposing wrongdoings or misconducts occurring within an organization. This study aimed to examine the perceived organizational support as a moderating variable of attitudes and perceived behavioral control. This study used a quantitative method with convenience sampling of 286-employees working in the public sector, which was then analyzed using hierarchical regression analysis. The results show that the perceived organizational support significantly played a role as a moderation influencing attitudes and perceived behavioral control over internal whistleblowing intentions. To improve internal whistleblowing intentions, organizations can create anonymous reporting channels and socialize whistleblowing systems.